Role of TNF block genetic variants in HIV-associated sensory neuropathy in black Southern Africans - Wadley, A.; Hendry, L.; Kamerman, P.; Chew, C.; Price, Patricia; Cherry, C.; Lombard, Z. (Nature Publishing Group, 2015)
HIV-associated sensory neuropathy (HIV-SN) is a common neurological complication of HIV infection. The TNF block is a region within the central MHC that contains many immunoregulatory genes. Polymorphisms and haplotypes of the TNF block have been associated with increased risk of HIV-SN in Asians and whites. Here we investigated genetic associations with HIV-SN in 342 black Southern Africans (190 cases and 152 neuropathy-free controls) using single nucleotide polymorphisms (SNPs) spanning the TNF block and a set of haplotypes defined by 31 SNPs in Asian and white populations (denoted FVa). We included population-appropriate tagSNPs derived from an African population (Yoruban, YRI, HapMap) and derived extended haplotypes comprising 61 SNPs (denoted FVa-ext b). We found no association between HIV-SN and carriage of two SNPs (TNF-1031/rs1799964*C and BAT1 (intron10)/rs9281523*C) associated with HIV-SN in whites and Asians. Additionally, a haplotype containing TNF-1031/rs1799964*C associated with increased risk of HIV-SN in Asians, but was not present in this African population. However, alleles of seven SNPs associated with reduced risk of HIV-SN (corrected for age, height and multiple comparisons). These were rs11796*A, rs3130059*G, rs2071594*C, NFKBIL1-62/rs2071592*A, rs2071591*A, LTA+252/rs909253*G, rs1041981*C. One haplotype (FV18-ext1), not containing these alleles, was associated with increased risk of HIV-SN after correction for age, height and multiple comparisons. Our results confirm the involvement of genes in the TNF block in altering risk for HIV-SN, but genotypes critical in this African population differed from those affecting HIV-SN in whites and Asians. These differences support the need for genetic association studies in diverse populations.